Respuesta :
Answer:
Statement (b) is equivalent to statement (c), but neither is equivalent to statement (a).
Step-by-step explanation:
Let [tex]F[/tex] denote that "Fido is our fish's name" and let [tex]R[/tex] denote that "Rex is our dog's name". The statements listed in this question would then become:
- (a) [tex]F \implies R[/tex];
[tex]F[/tex] implies [tex]R[/tex]. - (b) [tex]\lnot ((\lnot F) \land (\lnot R))[/tex];
not ((not [tex]F[/tex]) or (not [tex]R[/tex])). - (c) [tex]F \lor R[/tex];
[tex]F[/tex] or [tex]R[/tex].
Apply de Morgan's Law [tex]\lnot (P \land Q) \iff (\lnot P) \lor (\lnot Q)[/tex] to rewrite statement (b). Let [tex]P = (\lnot F)[/tex] and [tex]Q = (\lnot R)[/tex]. By de Morgan's Law:
[tex]\begin{aligned} & \lnot ((\lnot F) \land (\lnot R)) \\ \iff \; & \lnot (P \land Q)\\ \iff \; & (\lnot P) \lor (\lnot Q) && (\text{by de Morgan's Law}) \\ \iff \; & (\lnot (\lnot F)) \lor (\lnot (\lnot R)) \\ \iff \; & F \lor R\end{aligned}[/tex].
In other words, statement (b) [tex]\lnot ((\lnot F) \land (\lnot R))[/tex] is equivalent to statement (c) [tex]F \lor R[/tex].
Statement (a) [tex]F \implies R[/tex] isn't equivalent to [tex]F \lor R[/tex].
For example, when [tex]F = \texttt{True}[/tex] and [tex]R = \texttt{False}[/tex], [tex]F \implies R[/tex] would be false since [tex]\texttt{True}[/tex] does not imply [tex]\texttt{False}[/tex]. However, for the same [tex]F[/tex] and [tex]R[/tex], [tex]F \lor R[/tex] would be true since [tex]F = \texttt{True}\![/tex].